Navigating the challenges of COVID-19: a case study of construction worker camps in Thailand - Sanongdej, Wanna; Junda, Tiraporn; Piaseu, Noppawan; Kraithaworn, Phachongchit; Krongthaeo, Suphanna; Keawpugdee, Jantra; Kongcheep, Saowaros; Noinam, Suwatjana; Tantiprasoplap, Sukanya; Srisuk, Wasana (Frontiers in Built Environment, 2025)
This paper explores how Thailand adeptly navigated the challenges posed by the COVID-19 outbreak, focusing on the collaboration between governmental authorities and the private sector. A specific camp designated for construction workers exemplified this successful management, despite the susceptibility of camp personnel from diverse nationalities and cultures to unrest in epidemic circumstances and confined environments. The organization systematically implemented various measures to address the epidemic challenges within the camp. This investigation aimed to understand how workers’ camps could effectively address this crisis and adapt to prevailing circumstances. Qualitative data were gathered through interviews with 15 construction workers and a focus group discussion with 5 health professionals (comprising 4 community nurses and a doctor). The data were subjected to content analysis in the Thai language. The findings illuminated four principal dimensions: 1) communication, 2) the establishment of appropriate management protocols, 3) prompt care, equitable engagement, and consistent oversight, and 4) a hygienic environment promoting innovation in construction. These insights will inform future strategies for managing epidemic diseases in establishments or worker camps. Furthermore, the study highlighted the importance of training programs that empower workers with knowledge about health practices and safety measures, ensuring they are well-equipped to navigate potential health threats.